Novel micro-nano epoxy composites for electronic packaging application: Balance of thermal conductivity and processability. (16th June 2021) - Hu, Yang; Chen, Chao; Wen, Yingfeng; Xue, Zhigang; Zhou, Xingping; Shi, Dean; Hu, Guo-Hua; Xie, Xiaolin
Abstract: Epoxy (EP) composites with comprehensive good processability, low coefficient of thermal expansion (CTE), and high thermal conductivity, but electrical insulation properties are largely demanded in the higher power electric devices. However, micro-fillers have a positive effect on maintaining the good flowability of epoxy composites, while do not bring high thermal conductivity enhancement per unit mass. While nano-fillers with high specific surfaces offer very promising opportunities for heat-conducting network construction, but the nano-fillers dispersion is difficult to control and will cause increased viscosity and processing difficulties. Herein, we expect that the addition of small amounts of silver nanowires (AgNWs) at 0.5 vol% into the EP/S-Al2 O3 composites could largely enhance the thermal conductivity but not sacrifice their processability. Owing to the bridging effects of rigid nanowires between the main spherical particles, the thermal conductivity of the micro-nano EP/AgNWs/ S -Al2 O3 composites with 40 vol% S -Al2 O3 and 0.5 vol% AgNWs exhibits a 106.5% increment comparing to that without AgNWs. The limitation of both single micro or nano-sized thermal conductive fillers can be offset by the micro-nano filler network structure. The best combination properties of the EP/AgNWs/ S -Al2 O3 composites can reach the high thermal conductivity (1.602 W/m·K), low viscosity (55.6 Pa s), low CTE (37.1 ppm/°C), and high glass transition temperature ( T g, 152.1 °C). These results demonstrate that adding multiscale fillers into epoxy composites may solve the tradeoff between thermal conductivity and processability performances and fit the applications in high-power density electronic devices. Graphical abstract: The cost-effective epoxy-based underfill materials with high thermal conductivity play a critical role in the performance and reliability of rapidly developed microelectronic products. A novel epoxy composites with multiscale micro-nano filler structure are developed to overcome the limitation of only adding single micro- or nano-sized thermal conductive fillers to achieve higher thermal conductivity and better processibility simultaneously. Image 1